The Story of the Prophet Moses and the Pharaoh in the Qur'an: An Analysis of the Implementation of Structural Da'wah - Fadli, Muhamad Aroka; Sarbini, Ahmad; Kosasih, Engkos (Hanifiya: Jurnal Studi Agama-Agama, 2024)
The story of Prophet Moses (Moses) and Pharaoh (Pharaoh) is the most frequently mentioned narrative in the Qur'an, appearing in as many as 296 verses. The repetition of this story underscores its significance and the lessons it holds, especially regarding relations with leaders. Scholars such as Sayyid Qutb, Hasan al-Banna, and al-Mawardi emphasize the obligation of Muslims to preach to unjust leaders using religious teachings. Allah warns of the dire consequences of a leader's injustice, including painful punishment and the destruction of a nation. Therefore, da'wah (preaching) to leaders becomes a crucial step. The research methodology includes collecting verses related to the story of Prophet Moses and Pharaoh, carefully examining the words and sentences used in these verses, studying the interpretations from various schools of thought, and conducting a thorough analysis using objective reasoning and philosophical and allegorical methods (ishari) as approached by al-Ghazali. The results of this study indicate that the implementation of da'wah from the story of Prophet Moses with Pharaoh is that despite numerous challenges from tyrannical regimes, Prophet Moses remained steadfast and patient in carrying out his ministry. Prophet Moses' style of discussion and reasoned debate demonstrates the value of a preaching strategy that focuses on both spiritual and intellectual strength. Prophet Moses' attitude demonstrates how a preacher must be courageous, patient, and consistent when dealing with opposing powers.